Photocatalytic Activity of ZnxMn3−xO4 Oxides and ZnO Prepared From Spent Alkaline Batteries - Alcaraz, Lorena; Jiménez-Relinque, Eva; Plaza, Lorenzo; García-Díaz, Irene; Castellote, Marta; López, Félix A. (Frontiers in Chemistry, 2020)
Oxides with ZnxMn3-xO4 stoichiometry’s and ZnO were synthetized from black mass from spent alkaline batteries. The oxides were characterized through XRF, XRD with Rietveld refinement, SEM and TEM microscopy. Optical characterization included diffuse reflectance (DRS) and photoluminescence (PL) measurements. ZnO presented a clear band-edge in the UV region and PL signals were detected. Zn/Mn oxides presented a strong absorption in the UV region and continuous absorption band in the Vis-IR regions. There is non detected PL signal due to excited charges could be trapped on sub-bands energy states and/or transfer by non-radiative paths. Photocatalytic activity under both irradiation has been evaluated using the resazurin dye test, terephthalic acid fluorescence probe method, and NOx air purification evaluation. In the three photoactivity performed tests, ZnO shown good results under both UV-Vis irradiations, while there is no evidence of any appreciable photocatalytic activity of Zn/Mn. The results are discussed in terms of the findings of optical measurements that have been reported.